The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1002/1873-3468.14590
|View full text |Cite
|
Sign up to set email alerts
|

Two phosphoenolpyruvate carboxykinases with differing biochemical properties in Chlamydomonas reinhardtii

Abstract: Phosphoenolpyruvate carboxykinase (PEPCK) catalyses the reversible reaction of decarboxylation and phosphorylation of oxaloacetate (OAA) to generate phosphoenolpyruvate (PEP) and CO2 playing mainly a gluconeogenic role in green algae. We found two PEPCK isoforms in Chlamydomonas reinhardtii and we cloned, purified and characterised both enzymes. ChlrePEPCK1 is more active as decarboxylase than ChlrePEPCK2. ChlrePEPCK1 is hexameric and its activity is affected by citrate, phenylalanine and malate, while ChlrePE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…5A) is close to the EC50 of Gln Chellamuthu et al (2014) determined for the activation of NAGK by the PII protein (2.4  0.8 mM), suggesting that both regulatory effects might be operative under similar physiological conditions. Rather recently, it was shown that Chlamydomonas phosphoenolpyruvate carboxykinase isoform 2 is inhibited by Gln (Torresi et al, 2023) is shown as gray cartoon, except for the ACT domains, in which consecutive -helices and -strands were colored in shades of green. The AMA2 dimer model and the HvAMY2 structure (purple cartoon)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5A) is close to the EC50 of Gln Chellamuthu et al (2014) determined for the activation of NAGK by the PII protein (2.4  0.8 mM), suggesting that both regulatory effects might be operative under similar physiological conditions. Rather recently, it was shown that Chlamydomonas phosphoenolpyruvate carboxykinase isoform 2 is inhibited by Gln (Torresi et al, 2023) is shown as gray cartoon, except for the ACT domains, in which consecutive -helices and -strands were colored in shades of green. The AMA2 dimer model and the HvAMY2 structure (purple cartoon)…”
Section: Discussionmentioning
confidence: 99%
“…5A) is close to the EC 50 o f Gln Chellamuthu et al (2014) determined for the activation of NAGK by the P II p rotein (2.4 ± 0.8 mM), suggesting that both regulatory effects might be operative under similar physiological conditions. Rather recently, it was shown that Chlamydomonas phosphoenolpyruvate carboxykinase isoform 2 is inhibited by Gln (Torresi et al, 2023), representing an additional example of a direct effect of Gln. It appears that the alga employs Gln as a signaling molecule to coordinate N- and C metabolism directly at the enzymatic level in diverse contexts, and that AMA2 might be an additional example.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, oxaloacetic acid and acetyl-CoA cannot be converted into citric acid in time and enter the TCA cycle ( Llamas-Ramirez et al, 2020 ; Tovilla-Coutino et al, 2020 ; Jezewski et al, 2021 ), ultimately affecting Fp metabolism and physiological balance. Phosphoenolpyruvate, as a crucial intermediate linking glycolysis and the TCA cycle, contributes to the amount of ATP required for cellular energy metabolism ( Torresi et al, 2023 ). Oxaloacetate and pyruvate are catalyzed by PEPCK and PEPs to generate phosphoenolpyruvate, TM28 downregulates the expression of PEPCK, and PEPs further inhibit TCA cycling and ATP energy production in Fp .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the EC 50 value of 2.1 ± .7 mM of Gln we determined for AMA2 activation (Figure 5a ) is close to the EC 50 of Gln Chellamuthu et al ( 2014 ) determined for the activation of N ‐acetyl‐L‐glutamate kinase by the P II protein (2.4 ± .8 mM), suggesting that both regulatory effects might be operative under similar physiological conditions. Rather recently, it was shown that Chlamydomonas phosphoenolpyruvate carboxykinase isoform 2 is inhibited by Gln (Torresi et al, 2023 ), representing an additional example of a direct effect of Gln. It appears that the alga employs Gln as a signaling molecule to coordinate N and C metabolism directly at the enzymatic level in diverse contexts and that AMA2 might be an additional example.…”
Section: Discussionmentioning
confidence: 99%